A case of paragonimiasis inducing bilateral pneumothorax with lung and liver involvement. (March 2022) - Ha, Ji Sung; Lee, Jang Young; Sung, Won Young; Seo, Sang Won; Lee, Won Suk
Pulmonary paragonimiasis can occasionally induce bilateral pneumothorax and cause lesions in ectopic organs such as the liver. We report the case of a 26-year-old man who had been treated for bilateral hydropneumothorax one month earlier and returned to the emergency center complaining of epigastric pain that had persisted for four months. After being diagnosed with pulmonary and hepatic paragonimiasis, he was treated with praziquantel and his condition improved without complications.